Implementation strategy of harmony between ethnics among youths in Malaysia through National Service - Ismail, Mohd Mahadee; Mohd Noor, Mansor; Hassan, Nor Azlili; Abdullah, Nor Hafizah; Abdullah, Azlina (Human Resource Management Academic Research Society, 2020)
This paper discusses the implementation strategy to achieve harmony between ethnic groups among the Malaysian youths. The study focuses on Universiti Putra Malaysia (UPM) students who have joined the National Service Training Program (PLKN). PLKN is a national agenda which aims to train the young people to be an excellent future generation, especially in the context of multiethnic Malaysians. The main goal of PLKN's implementation is; (i) to enhance the spirit of patriotism and love the nation among the younger generation; (ii) to foster national unity and national integration; (iii) to develop positive character through the application of good values; (iv) to promote the spirit of volunteerism among the youth; and (v) to produce a young generation with strong physical and mental as well as high self esteem. There are 207 respondents participated in this study which is comprising of Malay and Chinese youths. The findings show that almost all measured dimensions are at a high level of intensity. The intensity of the Malay youths was higher than the Chinese youths. In general, the implementation of PLKN is the best strategy in establishing harmony among ethnic groups, especially among youths who are the future generation of the nation. However, the national service program has been abolished after the conversion of the federal government in the 14th General Election.